Rating and reliability assessment of a historical masonry arch bridge - Alpaslan, Emre; Yilmaz, Mehmet Fatih; Sengönül, Burcu Dinc (SPRINGER HEIDELBERG, 2023)
Historical masonry bridges constitute an essential part of the existing road and railway bridges. These bridges have been used for many years and have been preserved as a cultural resource. However, natural disasters have damaged or destroyed many of these historic bridges. In addition, it is crucial to ensure that historic bridges, which are still in use on some critical routes, provide safe service under increasing vehicle loads. Linear analysis approaches have been used to determine the behavior of existing historical bridges under vertical loads. However, these approaches do not give sufficient information and results to evaluate the actual capacities of bridges and result in an underestimation of the capacity of the bridges which is not appropriate from an economic point of view. Thus, further research focuses on the more advanced analysis to identify the real capacity of masonry arch bridges. The main purpose of this study is to evaluate load-carrying capacity and perform reliability analysis of an existing historical arch bridge using the response surface-based finite element model calibration process to present crucial references for the capacity evaluations of other similar masonry arch bridges. The experimental study was conducted to identify modal parameters of the masonry bridge by employing the operational modal analysis method under environmental effects. Using the modal parameters obtained from the experimental study, the approach that allows the initial finite element model of the bridge to be calibrated autonomously has been applied to create a more realistic finite element model of the bridge. Moreover, the vertical load-carrying capacity of masonry bridges with the help of nonlinear approaches was determined, and the nonlinear load-carrying capacity was used in the rating analysis of the bridge. Finally, rate ratios representing the actual performance of the bridge were obtained.
Keywords: Finite element model updating; Reliability analysis; Masonry arch bridges; Nonlinear analysis; Response surface method; UNIAXIAL COMPRESSIVE STRENGTH; MODULUS; MODEL; Engineering